1988
DOI: 10.1073/pnas.85.21.7932
|View full text |Cite
|
Sign up to set email alerts
|

A 22-nucleotide spliced leader sequence in the human parasitic nematode Brugia malayi is identical to the trans-spliced leader exon in Caenorhabditis elegans.

Abstract: A 22-nucleotide spliced leader sequence in the human parasitic nematode Brugia malayi is identical to the trans-spliced leader exon in Caenorhabditis elegans ( Communicated by Lester 0. Krampitz, July 25, 1988 (received for review June 6, 1988 ABSTRACTThe mRNAs encoding a 63-kDa antigen in the human parasitic nematode Brugia Malayi contain a spliced leader sequence of 22 nucleotides (nt) that is identical to the trans-spliced leader found on certain actin mRNAs in the distantly related nematode Caenorhabditis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 15 publications
3
39
0
Order By: Relevance
“…Figure 1A shows the hybridization of this complementary sequence, 5'-dCTCAAACTTGGGTAATTAAACC-3', to DNAs of C. elegans and 0. volvulus restricted by three different enzymes. The probe hybridizes predominantly to a 930-bp fragment in the Avall, DdeI, and HindIII digests of C. elegans DNA, as predicted from the earlier demonstration that this sequence is encoded within the repeat unit containing the C. elegans 5S rRNA gene (28). In contrast, the probe hybridizes to more than 30 different fragments in the digests of 0. volvulus DNA.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Figure 1A shows the hybridization of this complementary sequence, 5'-dCTCAAACTTGGGTAATTAAACC-3', to DNAs of C. elegans and 0. volvulus restricted by three different enzymes. The probe hybridizes predominantly to a 930-bp fragment in the Avall, DdeI, and HindIII digests of C. elegans DNA, as predicted from the earlier demonstration that this sequence is encoded within the repeat unit containing the C. elegans 5S rRNA gene (28). In contrast, the probe hybridizes to more than 30 different fragments in the digests of 0. volvulus DNA.…”
Section: Resultsmentioning
confidence: 84%
“…Recently, it has been observed that 10 to 15% of the mRNAs of several nematodes, including Caenorhabditis elegans and Brugia malayi, also possess a 5' SL of 22 nucleotides whose sequence is unrelated to the 39-nucleotide SL of trypanosomes (16,28). For example, in C. elegans three of the four actin mRNA species contain this nematode SL at their 5' ends, while the fourth actin mRNA does not (16).…”
mentioning
confidence: 99%
“…This gene (BmATS) encodes an asparaginyl tRNA synthetase of B. malayi, and its mRNA was the first to be shown to be trans-spliced in this parasite [19]. To obtain a clone containing the promoter and downstream domains of the BmATS gene, the gene was identified by a BLAST search of The Institute for Genomic Research (TIGR) genomic sequence (available from the TIGR B. malayi genome project at http://www.tigr.org/tdb/e2k1/bma1/intro.shtml), using the full length mRNA sequence (Genbank Accession number J03266) as the query.…”
Section: Preparation Of Parental Constructsmentioning
confidence: 99%
“…To answer the first question, a portion of the B. malayi asparaginyl tRNA synthetase (BmATS) gene was isolated and tested for its ability to direct trans-splicing. The BmATS gene encodes the first mRNA shown to be trans-spliced in B. malayi [19] and it contains a perfect homologue of the BmHSP70 TSM in its first intron (Figure 4, panel A). A construct (BmATS E1-I1-E2-luc) containing the 544 nt upstream of the ORF, the first exon, the first intron and 11 nt of the second intron ( Figure 4, Panel A) was cloned upstream from the luciferase reporter gene of pGL3 basic and transfected into B. malayi embryos.…”
Section: Activity Of the Bmhsp70 Tsm In Other Genesmentioning
confidence: 99%
“…The C. elegans SL1 sequence is encoded within the spacer region of the repetitive DNA element containing the 5S rRNA gene cluster and transcribed from the complementary strand to an RNA of about 100 nucleotides by RNA polymerase II during early embryonic development, just like U1 snRNA molecules in vertebrates. Linkage between the 5S rRNA gene and the SL1 RNA exon within a repetitive DNA element has also been found in other nematodes such as Onchocerca volvulus [17], Dirofilaria immitis [17], Brugia malayi [13], and Ascaris lumbricoides [14]. Although the 5S rRNA and SL1 loci in C. elegans are on complementary strands of the repetitive DNA element, the two loci for 5S rRNA and SL1 are on the same strand in the parasitic nematodes, O. volvulus, D. immitis, B. malayi, and A. lumbricoides.…”
mentioning
confidence: 99%